2013
DOI: 10.1021/jp408821a
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Evaluation of Multiple Rotationally Excited States of H3+, H3O+, and CH5+ Using Diffusion Monte Carlo

Abstract: An extension to diffusion Monte Carlo (DMC) is proposed for simultaneous evaluation of multiple rotationally excited states of fluxional molecules. The method employs an expansion of the rotational dependence of the wave function in terms of the eigenstates of the symmetric top Hamiltonian. Within this DMC approach, each walker has a separate rotational state vector for each rotational state of interest. The values of the coefficients in the expansion of the rotational state vector associated with each walker,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 86 publications
0
13
0
Order By: Relevance
“…The zero-point energy is evaluated by taking the time-averaged value of V ref (τ) in eq . In the expression for V ref , V̅ is the average potential energy of the ensemble, α is 0.5/Δτ, , and N w (τ) is the number of walkers at imaginary time τ. Once equilibrated, the density of the walkers near the molecular configuration represented by the coordinates, x , is proportional to the value of the ground state wave function at that geometry.…”
Section: Diffusion Monte Carlomentioning
confidence: 99%
“…The zero-point energy is evaluated by taking the time-averaged value of V ref (τ) in eq . In the expression for V ref , V̅ is the average potential energy of the ensemble, α is 0.5/Δτ, , and N w (τ) is the number of walkers at imaginary time τ. Once equilibrated, the density of the walkers near the molecular configuration represented by the coordinates, x , is proportional to the value of the ground state wave function at that geometry.…”
Section: Diffusion Monte Carlomentioning
confidence: 99%
“…The development of accurate potential energy and electric dipole moment hypersurfaces 182,183 for CH + 5 allowed the quantum-chemical characterization of the rovibrational dynamics of CH + 5 . Earlier studies 178,[184][185][186][187][188][189][190][191][192][193][194][195] yielded rovibrational energy-level patterns that even qualitatively differ from the results of variational nuclear-motion computations. 55,[196][197][198] The variational results also revealed that the rovibrational energy-level pattern of CH + 5 defies any interpretation attempts based on the standard RRHO model.…”
Section: Ch + 5 and The Vibrational Quantum-graph Modelmentioning
confidence: 99%
“…A more complete description of the theory and our implementation can be found in earlier publications. 18,22,24,25,27 Briefly, the algorithm that we use is based on the studies of Anderson. 23, 27 The approach derives from the parallel structure of the diffusion equation, which includes a coordinate-dependent rate process…”
Section: ■ Theorymentioning
confidence: 99%
“…The details of the simulation approach have been described previously. 22 The most significant change is the introduction of a potential energy term in eq 15. For this study, V(ϕ) is evaluated at the position of each walker at each time step.…”
Section: ■ Theorymentioning
confidence: 99%